Reconstituting Immune Surveillance in Breast Cancer: Molecular Pathophysiology and Current Immunotherapy Strategies - Chiara Cilibrasi (MDPI AG, 2021)
Over the past 50 years, breast cancer immunotherapy has emerged as an active field of research, generating novel, targeted treatments for the disease. Immunotherapies carry enormous potential to improve survival in breast cancer, particularly for the subtypes carrying the poorest prognoses. Here, we review the mechanisms by which cancer evades immune destruction as well as the history of breast cancer immunotherapies and recent developments, including clinical trials that have shaped the treatment of the disease with a focus on cell therapies, vaccines, checkpoint inhibitors, and oncolytic viruses.